2008
DOI: 10.1016/j.ccr.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Bcr-Abl-Positive Leukemic Stem Cells Is Dependent on Hedgehog Pathway Activation

Abstract: Resistance of Bcr-Abl-positive leukemic stem cells (LSCs) to imatinib treatment in patients with chronic myeloid leukemia (CML) can cause relapse of disease and might be the origin for emerging drug-resistant clones. In this study, we identified Smo as a drug target in Bcr-Abl-positive LSCs. We show that Hedgehog signaling is activated in LSCs through upregulation of Smo. While Smo(-/-) does not impact long-term reconstitution of regular hematopoiesis, the development of retransplantable Bcr-Abl-positive leuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
380
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(402 citation statements)
references
References 50 publications
16
380
2
2
Order By: Relevance
“…Mounting evidence indicate that hedgehog signaling is required for maintenance of cancer stem cell population (Dierks et al, 2008;Read et al, 2009;Zhao et al, 2009). For example, recent studies indicate that leukemia stem cells maintenance and expansion is dependent on hedgehog signaling (Dierks et al, 2008;Zhao et al, 2009).…”
Section: Activation Of Hh Signaling In Extracutaneous Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence indicate that hedgehog signaling is required for maintenance of cancer stem cell population (Dierks et al, 2008;Read et al, 2009;Zhao et al, 2009). For example, recent studies indicate that leukemia stem cells maintenance and expansion is dependent on hedgehog signaling (Dierks et al, 2008;Zhao et al, 2009).…”
Section: Activation Of Hh Signaling In Extracutaneous Tumorsmentioning
confidence: 99%
“…For example, recent studies indicate that leukemia stem cells maintenance and expansion is dependent on hedgehog signaling (Dierks et al, 2008;Zhao et al, 2009). In the absence of Smo or treatment of cyclopamine, the hematopoietic stem cell population is dramatically reduced.…”
Section: Activation Of Hh Signaling In Extracutaneous Tumorsmentioning
confidence: 99%
“…Combined therapy with TKIs plus agents that target other aspects of LSCs, such as hedgehog pathway inhibitors, is one strategy to control LSC proliferation and potentially provide deeper molecular responses and prevent relapse after TKI cessation. The hedgehog signaling pathway is activated in LSCs derived from patients with CML and is required for LSC maintenance [63,64]; combined treatment with nilotinib and the smoothened inhibitor LDE225 depleted LSCs and reduced LSC bone marrow engraftment in a mouse model of CML-CP [65]. A phase 1 trial of nilotinib and LDE225 in patients with CML-CP or CML-AP who have resistance to prior TKIs is ongoing.…”
Section: Targeting Lscs To Reduce the Risk Of Relapsementioning
confidence: 99%
“…Various studies have shown that PTEN/PI3K/Akt/Wnt signalling axis plays a vital role in maintenance of normal as well as malignant stem cell homeostasis [98][99][100], [88], [101][102][103][104]. Similarly, hedgehog signalling has been shown to play a role in regulating normal and malignant stem cells [105][106][107]. Notch signalling is known to regulate CSC maintenance [108,109].…”
Section: Cscs and Microenvironmentmentioning
confidence: 99%